Determining the diagnostic cut-off on the Chinese version of severity of dependence scale for cannabis - Albert Kar Kin Chung; Cheuk Yin Tse (Frontiers in Psychiatry)
IntroductionCannabis use and misuse are surging among the Chinese community in East and Southeast Asia. A quick screening instrument that can effectively identify users with dependence for early intervention is in utmost need. This study examined the psychometric properties of the Chinese version of the Severity of Dependence Scale for cannabis (C-SDS-C) in screening for the DSM-5 defined Cannabis Use Disorder (CUD).MethodsA retrospective chart review was conducted on Chinese-speaking individuals reporting cannabis use from three different substance use studies. Their demographic data, frequency of cannabis use within the past 30 days, scorings for the C-SDS-C and the severity of CUD at baseline were analyzed.ResultsThe C-SDS-C exhibited high reliability (Cronbach’s alpha = 0.778). It had a strong correlation with the severity of CUD (r = 0.456, p <.001) and a moderate correlation with the frequency of cannabis use within the past 30 days (r = 0.335, p = .001). All items loaded into a single factor which accounted for 56.64% of the variance. Receiver operating characteristic analysis demonstrated that a C-SDS-C cut-off score of ≥ 3 provided optimal discrimination for moderate to severe CUD among Chinese-speaking individuals using cannabis.ConclusionThe C-SDS-C is a valid and reliable screening instrument to identify cannabis users with moderate-to-severe CUD in the Chinese-speaking population.